Implementation in Russia and the European Union of International Safety Standards of Identity Documents with Biometric Data: Legal Regulation and Perspectives - A. G. Volevodz (Vestnik MGIMO-Universiteta)
RETRACTEDThe article contains the findings of a research into particular aspects of use of identity documents with personal biometric data. It considers the international safety standards of documents with biometric data worked out by the International Civil Aviation Organization (ICAO), pursuant to which those data should be included into machine-readable documents used by their holders for travel to various states. It contains the information on the implementation of these international standards in Russian and European Union law. The author has substantiated a conclusion to the effect that the procedure established in Russia for production and issuance, as well as for use of international, diplomatic and service passports identifying the Russian Federation citizen outside the Russian Federation territory, containing electronic information carriers with personal and biometric personal data, currently conforms to the international safety standards of documents with biometric data. The article surveys the experience of introducing domestic biometric identity documents - electronic passports in various countries of the world, and the problems arising therefrom. It substantiates the advantages and disadvantages of determining a passport of the Russian Federation citizen issued in the form of an identity card with an electronic information carrier, as the main document of the Russian Federation citizen identifying him domestically within the country's territory.